1990
DOI: 10.2337/diacare.13.5.529
|View full text |Cite
|
Sign up to set email alerts
|

Low-Pigment Skin Type and Predisposition for Development of Type I Diabetes

Abstract: To ascertain whether skin pigmentation type and sensitivity to ultraviolet (UV) light are associated with susceptibility to type I (insulin-dependent) diabetes, 55 type I diabetic patients were examined, 38 new-onset and 17 long-term cases. They were compared to 72 control subjects of the same geographic region and nationality. To evaluate the individual skin pigmentation type, a standardized questionnaire was developed. Reactivity to UV light was determined by a stepwise-graded UV irradiation. Significantly m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…Significantly more diabetic patients in southern Germany had blue eyes than nondiabetic control subjects, while the macular edema was more prevalent in blue- or grey-eyed diabetic persons in comparison to those with intermediate or brown eyes [4, 5]. Eleven percent from Italian women with rectovaginal endometriosis were with green or blue eyes, while only 3% of healthy controls were with light eyes [10].…”
Section: Discussionmentioning
confidence: 99%
“…Significantly more diabetic patients in southern Germany had blue eyes than nondiabetic control subjects, while the macular edema was more prevalent in blue- or grey-eyed diabetic persons in comparison to those with intermediate or brown eyes [4, 5]. Eleven percent from Italian women with rectovaginal endometriosis were with green or blue eyes, while only 3% of healthy controls were with light eyes [10].…”
Section: Discussionmentioning
confidence: 99%
“…Fair skin and skin sensitivity to the sun have previously been significantly associated with T1DM with odds ratios of 3.4 and 5.8, respectively (3). This skin phenotype, as well as red hair, is over‐represented among individuals with reduced function variants of the melanocortin receptor 1 (MC1R) genotype (12).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D synthesis, per UVR dose, is increased up to six‐fold among those with fair compared to very darkly pigmented skin (2). Yet, the only study to examine skin phenotype and T1DM to date reported in 1990 that fair skin was associated with increased, not decreased, T1DM risk (OR 3.4, P = 0.003) (3). This important observation has not been examined in any subsequent studies.…”
Section: Introductionmentioning
confidence: 99%
“…K awamori et al (1) give impressive data of their ultrasound measurements of the carotid artery wall. The results concerning the great majority of their patients (275 NIDDM patients) are evident.…”
Section: Comments On "Prevalence Of Carotid Atherosclerosis In Diabetmentioning
confidence: 99%
“…Eye color and IDDM I t has been shown that a relatively large proportion of IDDM patients in southern Germany have a low-pigment eye color (blue or green) compared with nondiabetic control subjects (66 vs. 38%, P < 0.01) (1). Although no studies exist concerning the exact percentage, it is commonly accepted that dark eye colors prevail among Greeks.…”
mentioning
confidence: 99%